The development of the mammalian dentition as a complex adaptive system - Alan H. Brook; Toby E. Hughes; Grant C. Townsend; Richard N. Smith; Matthew D. Brook O'Donnell (Dental Anthropology Association, 2013)
General characteristics of Complex Adaptive Systems include self-adaptation and organisation, emergence, multitasking, robustness, critical phases, diversity and compatibility with such statistical models as Thresholds and Scale Free Networks. The aim was to investigate whether dental development exhibits the general and statistical characteristics of a Complex Adaptive System, by examining data on normal and abnormal dental development. The findings were that self-adaptation and organisation occur while interactions between genes, epigenetic and environmental factors lead to the emergence of cells, tooth germs and mineralised teeth. Multitasking occurs as signalling pathways act simultaneously and reiteratively during initiation and morphogenesis. Tooth germs that do not attain a critical threshold during development may undergo apoptosis. Diversity is evident in tooth number, size, shape and mineralisation. Statistical investigation shows that males have significantly larger teeth and higher prevalences of megadontia and supernumerary teeth (p<0.05), supporting Brook's Threshold Model which is further developed here to include shape. Image Analysis of tooth dimensions showed they followed a Power Law distribution, with the first 8 of 34 factors in upper lateral incisors accounting for 94.4% of the total variation. In conclusion, the development of the dentition shows the general and statistical characteristics of a Complex Adaptive System.